PENGARUH ABU CANGKANG KELOMANG SEBAGAI SUBSTITUSI SEMEN TERHADAP KUAT TEKAN BETON - Thifal, Ratu; Susilo, Alfred Jonathan; Sandjaya, Arif (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2026)
Cement production grows by around 5-6.5% per year. Cement is made from a mixture of materials, one of which is limestone, with a portion of 75-90%. Most limestone is formed from shells, skeletons, and remains of dead marine organisms that go through geological processes over thousands to millions of years. Therefore, alternative materials that are more environmentally friendly and sustainable are important to reduce cement use. Hermit crab shell ash was studied in this study as a partial substitute for cement in concrete mixtures. The substitution variations used were 0%, 3%, 5%, and 7% of the cement weight. The mixture plan fc' 25 MPa based on SNI 03-2834-2000. The test specimen was a 15x30 cm cylinder and was cured by immersion for 28 days based on SNI 2493:2011. Compression testing was based on SNI 1974:2023. The results showed a decrease in compressive strength, but not significantly. A 3% substitution yielded the best results compared to the others, with a reduction in compressive strength of around 2.3%. Hermit crab shells have the potential to be a sustainable alternative material to limestone without the need for geological processes that take thousands to millions of years. Abstrak Produksi semen tumbuh sekitar 5-6,5% per tahun. Semen terbuat dari campuran bahan, salah satunya adalah batu kapur dengan porsi 75-90%. Sebagian besar batu kapur terbentuk dari cangkang, kerangka, dan sisa-sisa organisme laut mati yang melalui proses geologis dengan waktu ribuan hingga jutaan tahun. Oleh sebab itu, material alternatif yang lebih ramah lingkungan dan berkelanjutan menjadi penting untuk mengurangi penggunaan semen. Abu cangkang kelomang dikaji dalam penelitian ini sebagai substitusi sebagian semen dalam campuran beton. Variasi substitusi yang digunakan yaitu sebesar 0%, 3%, 5%, dan 7% terhadap berat semen. Rencana campuran fc’ 25 MPa berdasarkan SNI 03-2834-2000. Benda uji berupa silinder 15x30 cm dan dirawat rendam selama 28 hari berdasarkan SNI 2493:2011. Pegujian tekan berdasarkan SNI 1974:2023. Hasil menunjukan nilai kuat tekan menurun, tetapi tidak signifikan. Subtitusi 3% memberikan hasil paling baik dibandingkan lainnya, dimana penurunan kuat tekan sekitar 2,3%. Cangkang kelomang memiliki potensi menjadi material alternatif berkelanjutan menggantikan batu kapur tanpa perlu melalui proses geologis dengan waktu ribuan hingga jutaan tahun.